Increasing Engagement and Effectiveness of Panel Discussions Exploring Gender and Sexual Identity - Gentry, Randall; Sharp, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Panels are effective ways of presenting course material. To enhance students’ ability to integrate course material during panel discussions, we offer several recommendations for instructors. Recommendations include: (a) providing panelists with key concepts from the class, and (b) assessing students’ knowledge of the topic before and after the panel discussion.